Avaliação dos efeitos da microadição de NbB na solidificação da liga de alumínio 2017 - Silva, Argos Soares (Universidade Federal de São Carlos, 2022)
The 2017 alloy, based on the Al-Cu system, is widely applied in the manufacture of structural parts in the aeronautical and automobile industries. In this work, the modification of this alloy through the addition of Nb and B was studied, which was done through the use of an Al-5%pNb-1%pB master alloy. Samples of alloy 2017 and alloy 2017 + NbB with thicknesses of 3 mm and 4 mm were produced by the centrifugal casting technique, thus providing high cooling rates. Mean grain sizes and interdendritic spacings were measured for the alloys with and without addition of Nb-B inoculant and with 3 mm and 4 mm thick. Vickers hardness tests were also performed for each of the samples, thus relating the microstructural conditions of grain size and interdendritic spacing of each sample with its mechanical properties. The results show that the samples without the addition of NbB presented a microstructure composed predominantly of columnar grains, while the samples with the addition of NbB presented a microstructure composed largely of equiaxed grains, with a reduction in the average grain size of more than 2 times. The variation in the thickness of the samples did not appear to have an effect on the average grain size. It was observed that the addition of the inoculant Nb-B did not seem to cause a variation in the interdendritic spacing for the samples with the same thickness, however the increase in the thickness of the samples caused a small reduction in the interdendritic spacing. In turn, the results of the Vickers hardness tests indicate that the introduction of the inoculant NbB caused an increase in the mechanical properties due to its grain refining effect.
Evaluation of NbB inoculation on the solidification of a 2017 alloy
Keywords: Ligas de Al; Refino de grão; Inoculação; Microestrutura de solidificação; Espaçamento interdendrítico; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA